VD_FINDINFO HC / 2020 / 251 vom 15. April 2020 - VD Tribunal cantonal (2020)
AUTORITÉ DE CONCILIATION, COMPÉTENCE, CONSORITÉ, BAIL À LOYER, COLOCATAIRE, DÉCISION D'IRRECEVABILITÉ | 29 al. 2 Cst., 210 CPC (CH), 212 CPC (CH), 236 al. 1 CPC (CH), 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 53 CPC (CH), 59 al. 2 let. c CPC (CH), 70 al. 1 CPC (CH)